Optimizing the Method of Cell Separation from Bile of Patients with Cholangiocarcinoma for Flow Cytometry - Yafei Xia; Yuan Gao; Botao Wang; Hui Zhang; Qi Zhang (Gastroenterology Research and Practice)
Analysis of the change of the cells in bile is an evolving research field in biliary pathophysiology and has potential value in diagnosis and therapy. However, laboratory studies of cell in bile across the world are scarce. Bile was collected from the clinical patients with cholangiocarcinoma (CC). To optimize the cell separation method in bile of patients with CC, we studied the factors that may affect cell vitality in bile including the dilution buffer, centrifugal force, centrifugal time, and store time and temperature. Then these factors were modified and performance was evaluated by flow cytometry with respect to the percentage and total yield of viable cells. The separated cells from bile were stained with CD3, CD4, CD8, CD56, TCRγ/δ, CD16, CD14, HLA-DR, CD33, CD15, CD11b, lineage cocktail (CD3, CD14, CD19, CD20, and CD56), CD66b, and CD45 antibodies. The different buffer solutions were joined in bile of patients with CC; experiment results show that the different dilutions have nearly no effect on the ratio of cells in bile by flow cytometry. The best centrifugal procedure was 300 g, 10 min. Bile should be stored at 4°C rather than at normal temperature. Our study further showed that the shorter time of the bile storage, the higher viability of the cell, and immune cells existed in cells isolated from bile. Evaluating bile cell viability is necessary to evaluate method performance.